Development of Palm Oil Purchasing System for Palm Oil Field in Ban Takrob, Chaiya District, Surat Thani Province - สุขเขียว ภัทรวิทย์; สอนเพชร พุทธรักษ์; จันปาน สุภาภรณ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims (1) to develop a palm oil purchasing system for the Ban Takrob palm yard, Chaiya District, Surat Thani Province and (2) to study the satisfaction of users of the palm oil purchasing system for the Ban Takrob palm yard, Chaiya District, Surat Thani Province. The system was developed using Google Appsheet, using Google sheet as the database, and using Line Application to create an automatic response chatbot. The research was conducted by collecting data from the satisfaction assessment form of the system users. The sample group used in the research was 1 officer (buyer) and 73 users (sellers). The purposive sampling method was used to select the research instruments based on the researcher’s decision in accordance with the research objectives. Three experts were asked to examine the research instruments (IOC). The instruments used for data collection were satisfaction assessment forms. The statistics used for data analysis were the mean and the standard deviation (S.D.). The research results consisted of (1) The palm oil purchasing system for the Ban Takrob palm yard helped in communicating and collecting palm oil purchasing data efficiently. (2) The results of the satisfaction assessment of the system users showed that the overall picture of the system operation and system design was at the highest level.